Preoperative Immersive Virtual Reality Planning and Simulation of Bronchoscopic Lung Volume Reduction Using Endobronchial Valves - Shotaro Okachi; Hideaki Takahashi; Hisashi Kako; Takuma Ina; Tomoya Horiguchi; Yasuhiro Goto; Yasushi Matsuda; Sumito Isogai; Naozumi Hashimoto; Michitaka Fujiwara; Kazuyoshi Imaizumi (Respirology Case Reports)
ABSTRACT Bronchoscopic lung volume reduction (BLVR) with endobronchial valves is an established treatment for selected patients with advanced emphysema. A 74‐year‐old male patient with chronic obstructive pulmonary disease and severe dyspnea was scheduled to undergo BLVR targeting the right middle lobe bronchus based on high‐resolution CT findings, which showed severe emphysematous changes with hyperinflation and fissure completeness of 98% in the right middle lobe. The physician conducted preoperative virtual reality (VR)‐assisted planning using the patient's imaging data, enabling comprehensive visualisation of the bronchial tree, airway measurements, and procedural simulation. The Chartis system confirmed a ‘no flow’ pattern, supporting the absence of collateral ventilation. During the procedure, a size 5.5 valve was placed in the right B4/5 bronchus following VR and intraoperative assessments. The patient remained stable postoperatively without complications. VR enhanced procedural planning by improving airway assessment, optimising valve sizing, and reducing cognitive load, leading to increased efficiency and operator confidence. Further research is warranted to validate the utility of VR in bronchoscopic interventions.